THE DEVELOPMENT OF APTITUDE TESTS FOR ACCOUNTANTS. - Carey, John L. (The Accounting Review, 1945)
Abstract The article presents information on the development of aptitude tests for accountants. The conviction prevails among certified public accountants that their profession stands on the threshold of great opportunity. To cross that threshold, to take advantage of the opportunity, they foresee that they will need strength and versatility. A profession can be no stronger than its personnel. The accountants in public practice frankly recognize that in order to keep pace with the demands which seem certain to be made upon the profession the coming generation of accountants will have to be better than the present one. These considerations have intensified the interest of practicing accountants in the question of how to get the best available men for their staffs and train them as rapidly as possible to assume positions of leadership. This heightened interest has been given formal expression in a project in selection of personnel, launched by the American Institute of Accountants in January 1944, which may profoundly affect the future of the profession.